2020
DOI: 10.1186/s12889-020-08820-4
|View full text |Cite
|
Sign up to set email alerts
|

Do people living in disadvantaged circumstances receive different mental health treatments than those from less disadvantaged backgrounds?

Abstract: Background: Socioeconomic status (SES) has been linked to treatment outcomes for mental health problems, whilst little to no literature has explored the effects of SES on access to both medication and psychological therapy. The aim of this study was to explore whether access to mental health treatments differed by SES. Methods: The North West Coast Household Health Survey (HHS) collected data from residents aged 18+ from across 20 disadvantaged and 8 less disadvantaged neighbourhoods in 2015, and from 20 disad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 24 publications
2
18
0
1
Order By: Relevance
“…The prevalence of anxiety or depression from the Understanding Society study in 2014 was 19.7% (22.5% females, 16.8% males) 24 based on the General Health Questionnaire (GHQ). The closest comparable study is probably the NIHR ARC North West Coast Household Health Survey, which administered the PHQ9 and GAD7 (although administered face-to-face) to 4,000 people in the North West of England, mainly living in deprived areas; in this study, 17% were depressed and 13% were anxious 25 . A recently published study used data from the 'Understanding Society COVID-19 web survey' and reported the population prevalence of clinically significant levels of mental distress to be 27•3%2 26 .…”
Section: Discussionmentioning
confidence: 95%
“…The prevalence of anxiety or depression from the Understanding Society study in 2014 was 19.7% (22.5% females, 16.8% males) 24 based on the General Health Questionnaire (GHQ). The closest comparable study is probably the NIHR ARC North West Coast Household Health Survey, which administered the PHQ9 and GAD7 (although administered face-to-face) to 4,000 people in the North West of England, mainly living in deprived areas; in this study, 17% were depressed and 13% were anxious 25 . A recently published study used data from the 'Understanding Society COVID-19 web survey' and reported the population prevalence of clinically significant levels of mental distress to be 27•3%2 26 .…”
Section: Discussionmentioning
confidence: 95%
“…The closest comparable study is probably the National Institute for Health Research Applied Research Collaboration North West Coast Household Health Survey, which administered the PHQ9 and GAD7 (face-to-face) to 4000 people in the north-west of England, mainly living in deprived areas; in this study, 17 % were depressed and 13 % were anxious. 25 A recently published study used data from the Understanding Society COVID-19 web survey, and reported the population prevalence of clinically significant levels of mental distress to be 27.3 %. 26 The study used the GHQ to identify clinically significant distress, and data collection was approximately 1 month after our data collection period, but despite these differences the GHQ prevalence was similar to that based on meeting the criteria for either anxiety or depression in this study, which was 27.7 %.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that 29 and 24% of the general population reported moderate-to-severe symptoms of anxiety during the initial outbreak of COVID-19 in China ( Wang et al, 2020 ) and the United Kingdom ( Fancourt et al, 2020 ), respectively. The percentages of moderate-to-severe anxiety in those countries were lower before the COVID-19 pandemic ( Huang et al, 2019 ; Giebel et al, 2020 ). Importantly, recent findings raise concern for the mental health of university students.…”
Section: Introductionmentioning
confidence: 98%